Model of Financial Communication to Reinforce Financial Literacy for Indonesian Society - Endang Haryani; Rini Darmastuti; Sri Winarso Martyas Edi (ULTIMA Comm, 2024)
Cases of financial fraud, investment scam and illegal financial activities in the society have become urgent problems and solutions must be resolved. One of the things that greatly affects the emergence of this problem is that many of our people have no understanding of finance. Financial communication and financial models are urgently needed by the society. The purpose of this paper is to map the concept of financial communication and model of financial communication. This paper is based on the results of research conducted with a constructivist approach to construct the concept of financial communication and model of financial communication. Data were obtained from the results of Focus Group Discussions with several experts in the field of finance and law. The results of this research are first, financial communication is an urgency in the lives of Indonesian people at this time. Second, financial communication is the process of conveying messages from the source of the message to the society as a communicant related to finance and financial literacy. Third, the financial communication model is an interactive and two-way communication with several criteria for several components. The components of this communication model are credible communicators, financial messages that suit the needs of the communicators, communicators who have certain criteria, media that suit the communicators and the last is the impact. The impact of this communication model is financial literacy for the society.